Did injury incidence in alpine ski racing change after equipment regulations? An evaluation based on the injury surveillance system of the Austrian Ski Federation - Platzer, H.-P.; Barth, M.; Giger, A.; Schröcksnadel, P.; Nachbauer, W. (Journal of Science and Medicine in Sport, 2021)
Objectives: To assess the effects of alpine competition equipment regulations from 2003, 2007 and 2012 on severe injury incidence. Design: Case study Method: Data originated from records of the injury surveillance system of the Austrian Ski Federation. Injuries from the seasons 2001-2017 were divided in four periods between the equipment regulations. For comparison of consecutive periods, risk ratios (RR = later period / preceding period) with 95% CI were calculated. Total severe injury events, events with severe knee injuries, and events with severe ACL injuries were separately investigated. Results: A significant increase of total severe injury incidence was found after the equipment regulation in 2003 (RR 1.52, 95% CI 1.00-2.31). None of the other comparisons revealed significance (p < 0.05) or statistical trends (p < 0.1). Only the minority (40%) of the RR showed a reduction in the injury incidence of the Austrian Ski Team (lowest RR 0.78). 60% of the RR increased after the regulations (highest RR 1.63). Conclusions: Even though statistical uncertainties remain, our findings allow the conclusion, that the implemented equipment regulations did not cause a noticeable reduction of injuries. The three analysed equipment regulations were not appropriate or were counteracted by other factors.